Product Development of Plara Dip and Plara Curry - Ratmanee, Parichat; Pichai, Sananthorn; Poratso, Yanisa (SciTech Research Journal, 2021)
The objective of this study was to investigate the suitable formula of plara (fermented fish) dip and plara curry. The results showed that protein content of plara-dip was 12.40%, plara curry was 10.78%. Plara-dip had the sodium chloride content as 2.26% and plara curry as 2.40%, which the results were in accordance in Thai community product standard. The plara-dip products had the number of total bacteria as 1.28 x 103 CFU/g, plara curry products had the number of total bacteria as 2.82 x 103 CFU/g, which the results were in accordance in Thai community product standard (134/2546). On the other hand, sensory acceptance of product development of plara-dip and plara curry was the most acceptable. There were no statistically significant differences (p>0.05).